An approach to the industry of hedge funds. - Mendes-Ribeiro, Mafalda (2013)
This PhD thesis analyses the hedge funds industry starting by decomposing the performance of hedge funds indexes through the period of 1998-2008,using two important databases indexes, the EDHEC Alternative Indexes and the CSFB/TREMONT Alternative Indexes, and finally comparing their performance with the MSCI World Index. The first purpose, stated in Part One, is to determine whether stylistic characterization exists across hedge funds strategies, regarding seven strategies: Convertible arbitrage, Emerging markets, Event driven, Fixed income arbitrage, Global macro, Long/Short Equity and Equity market neutral. The results of Part One reveal that there is no significant differences between the strategies analyzed, suggesting that the purity in each style is not as developed and accurate as we may suppose. Following this, we analyze another specific aspect of hedge funds: if seasonality behavior is present in monthly returns in hedge funds indexes. Part Two intends to determine whether seasonality exists, by comparing the performance of the two major representative indexes of hedge funds, regarding the same seven main strategies. The results suggest that there are significant higher returns in December, as well as lower and negative returns during the months of July, August and September. These results suggest that BLASH(Buy Low And Sell High) is possible in Hedge Funds management. Finally we study the important aspect of neutrality. The objective of Part Three is to determine if market neutral hedge funds strategies are exposed to the equity market or if they are really market neutral. Using two main data base hedge funds indexes, and comparing them to the MSCI World Index, from January 1998 till December, we perform a comparative analysis on the most representative and most interesting market neutral hedge funds strategies.We checked for this neutrality and analyze what kinds of strategies consistently performance diferently over time. Our resuts suggest that neutrality strategies in the so called arbitrage and pure alpha, do not perform differently from the traditional capital market, so managers must be prudent when combine such strategies into their portfolios.